THE ROLE OF TURNOVER INTENTION AND THE INFLUENCE OF WORK SATISFACTION ON EMPLOYEE PERFORMANCE IN KSU SINAR DANA MANDIRI - Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati; I Nengah Basma Wijaya (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine the effect of job satisfaction on turnover intention, job satisfaction on employee performance, turnover intention on employee performance, and job satisfaction on employee performance through turnover intention as a mediating variable in KSU Mandiri Dana Sinar. This study took 32 respondents to KSU Sinar Dana Mandiri to obtain direct and indirect influence. Data were analysed by using Partial Least Square (PLS) analysis to answer the problem formulation with the help of Smart PLS 3 program. The results of analyzed showed thats : 1). Job satisfaction has a negative and significant effect on turnover intention, 2). Job satisfaction has a positive and significant effect on employee performance, 3). Turnover intention has a negative and significant effect on employee performance, and 4). Turnover intention variable is able to be a mediating variable between job satisfaction and employee performance.